The Christmas you found me - Morgenthaler, Sarah (Heart of the wilderness, 2024)
"Northern Idaho cattle rancher Sienna Naples isn't actually looking to hire a husband two weeks before Christmas, despite the ad her best friend puts in their small town's newspaper on the day Sienna's year-long, brutal divorce finalizes. Her plan is to hide out in the dangerously beautiful Frank Church Wilderness until the holiday season is over, riding fences and ignoring her wounded heart. Sienna's family has taken care of this land for generations and Sienna can't imagine any other life. But at Christmastime, with her parents gone and her marriage finally over, it's full of memories...and incredibly lonely. Until a tall, handsome stranger and a little girl walk into her life and suddenly the holidays are alive again. It was just a joke, but when single father Guy Maple shows up to answer the ad, the handsome Montana construction worker isn't joking. Money is tight this Christmas, and Guy's four-year-old daughter Emma is dying of stage-five chronic kidney disease. She needs a kidney transplant, but if Guy can't prove that he can afford Emma's anti-rejection medications, his daughter isn't going to stay on the transplant list. Guy's willing to do anything, including marrying a stranger, to keep her safe. It's an impulsive marriage of convenience, and Sienna knows this isn't real, no matter how much she adores Emma or how well Guy fits in to the ranching life. But the more time she spends with her new family, the more she fears losing the fragile, feisty little girl and the kind, devoted, hard-working, incredibly attractive man who is her husband--but is it only in name?"--